A Novel SNOW3G-M Algorithm and Medical - M. Zaki, Rana; Bahjat Abdul Wahab, Hala (International Journal of Online and Biomedical Engineering, 2022)
In the past two years, the demand for the use of mobile networks has increased, due to what the world has been exposed to in the face of the COVID-19 pan-demic and the lack of communication between people. People resorted to using of mobile networks in light of the pandemic, and their importance has appeared in several aspects, such as automotives, media and entertainment, and healthcare. This growing demand for the mobile network led to the actual development of the 4G network in terms of providing the speed of transmission and encryption data to maintain security. In this paper, a new member of the SNOW 3G family was proposed, which is one of the fourth generation algorithms called SNOW 3G-M, which has a higher encryption speed in line with the capacity of modern CPUs and is expected to be a move to the fifth generation communication system in the future. The SNOW 3G-M keystream passes all of the tests for long key stream data, short key stream data, and initialization vector data sets.